Análise da distribuição espacial de voçorocas em domínio de rochas siliciclásticas: bacia do Rio Pandeiros-MG - Arnon Costa Pereira de Lima (2019)
Accelerated erosion often associated with severe sediment loss to drainage systems, is an important topic of geosciences. This research aims to achieve better understanding of the slope characteristics including the upper part of the regotlith, here denominated geocovers, may be associated with their predisposition to gullies development. It was conducted at the Pandeiros River basin, northern Minas Gerais, Brazil, which has a significant regional importance due to the occurrence of a swamp in its low course, a nursery of several fish species, of fundamental importance for the maintenance of the ecosystem of the middle course of the São Francisco river. The occurrence of gullying processes contributes to the siltation of this wetland and to the increasing environmental vulnerability of the area, taking into account the large amount of this type of erosion in the basin (215). The work also aims to propose a methodological approach to optimize the sampling performed in slopes where these gullies occur. For this, slope inclination measurements and identification of geomorphological sites were carried out, as well as the collection of samples of geocovers which were submitted in the laboratory to physical and chemical analysis. Results show that there is a morphological control in the distribution of the studied gullies, limited by slope breaks that reach the whole basin. The statistical treatment of the data, using Pearson's correlation (r2), gives a better understanding of the main attributes of the geocovers that influence each slope, allowing identifying the main characteristics of each of them and their homogeneity relations, revealing the occurrence of slope groupings based on geomorphological- geological data. The Principal Component Analysis made it possible to compare the five studied slopes with gully occurrence demonstrating that they are different regarding to the investigated geocovers parameters.